Differential perivascular microglial activation in the deep white matter in vascular dementia developed post‐stroke. (24th June 2022) - Hase, Yoshiki; Ameen‐Ali, Kamar E.; Waller, Rachel; Simpson, Julie E.; Stafford, Charlotte; Mahesh, Ayushi; Ryan, Lucy; Pickering, Lucy; Bodman, Caroline; Hase, Mai; Boche, Delphine; Horsburgh, Karen; et al.
Abstract: With the hypothesis that perivascular microglia are involved as neuroinflammatory components of the gliovascular unit contributing to white matter hyperintensities on MRI and pathophysiology, we assessed their status in stroke survivors who develop dementia. Immunohistochemical and immunofluorescent methods were used to assess the distribution and quantification of total and perivascular microglial cell densities in 68 brains focusing on the frontal lobe WM and overlying neocortex in post‐stroke dementia (PSD), post‐stroke non‐dementia (PSND) and similar age control subjects. We primarily used CD68 as a marker of phagocytic microglia, as well as other markers of microglia including Iba‐1 and TMEM119, and the myeloid cell marker TREM2 to assess dementia‐specific changes. We first noted greater total densities of CD68 + and TREM2 + cells per mm 2 in the frontal WM compared to the overlying cortex across the stroke cases and controls ( p = 0.001). PSD subjects showed increased percentage of activated perivascular CD68 + cells distinct from ramified or primed microglia in the WM ( p < 0.05). However, there was no apparent change in perivascular TREM2 + cells. Total densities of TREM2 + cells were only 10% of CD68 + cells but there was high degree of overlap (>70%) between them in both the WM and the cortex. CD68 and Iba‐1 or CD68 and TMEM119 markers were colocalised by 55%. Within the deep WM, 30% of CD68+ cells were co‐localised with fragments of degraded myelin basic protein. Among fragmented CD68+ cells in adjacent WM of PSD subjects, >80% of the cells expressed cleaved caspase‐3. Our observations suggest although the overall repertoire of perivascular microglial cells is not changed in the parenchyma, PSD subjects accrue more perivascular‐activated CD68+ microglia rather than TREM2+ cells. This implies there is a subset of CD68+ cells, which are responsible for the differential response in perivascular inflammation within the gliovascular unit of the deep WM. Abstract : Post‐stroke patients who develop dementia accrued more perivascular activated CD68 + microglia in the frontal white matter (FWM). This implies activated CD68 + cells are responsible for perivascular inflammation within the gliovascular unit of the FWM.